Genetic relatedness, virulence, and drug susceptibility of Campylobacter isolated from water and wild birds - Andrzejewska, Małgorzata; Grudlewska-Buda, Katarzyna; Śpica, Dorota; Skowron, Krzysztof; Ćwiklińska-Jurkowska, Małgorzata; Szady-Grad, Małgorzata; Indykiewicz, Piotr; Wiktorczyk-Kapischke, Natalia; Klawe, Jacek J. (Frontiers in Cellular and Infection Microbiology, 2022)
The aim of this study was to perform characteristics of Campylobacter isolated from wild birds (Black-headed gulls Chroicocephalus ridibundus and Great tits Parus major) and surface water samples (rivers, ponds, ornamental lakes, freshwater beaches). Material for research included 33 Campylobacter isolates. All the strains were isolated by different monitoring and surveillance plans. The prevalence of selected genes (flaA, cadF, iam, cdtB, wlaN, sodB, tet0) encoding virulence factors among Campylobacter spp. was assessed by PCR method. The genetic similarities of isolates were determined by Pulsed-Field Gel Electrophoresis (PFGE). Susceptibility of Campylobacter isolates to clinically important antimicrobials: erythromycin, tetracycline and ciprofloxacin, previously assessed by E-test, was presented in the character of drug susceptibility profiles depending on the origin of the isolates. The cadF, flaA, cdtB and sodB genes exhibited the highest detection rate. Statistically significant differences between the presence of cdtB and wlaN virulence genes were noted among different species of the isolates. No genetically identical isolates were found. The most numerous antibiotic susceptibility profile included strains susceptible to all antibiotics studied (profile A-33.3%), the second most common was the tetracycline - and ciprofloxacin-resistant (profile B-27.2%) and tetracycline-resistant profile (C-24.2%) respectively. The study revealed virulent properties of Campylobacter isolated from water samples and wild birds and high resistance rates to tetracycline and fluoroquinolones. The lack of genetic relatedness among strains isolated from water and birds may indicate other sources of surface water contamination with Campylobacter bacteria than birds. Also the presence of Campylobacter spp. in wild birds could have other environmental origin.